Case Report: The Role of Intravascular Ultrasonography in Patients Underwent Percutaneous Coronary Intervention - Oktaviono, Yudi Her; Putri, Alisia Yuana (Folia Medica Indonesiana, 2019)
Resveratrol is an antioxidant that can be used as anti-aging. Topical use has several problems because solubility in water is low and unstable to light. This study aimed to evaluate the effect of the combination of soy bean oil and oleic acid liquid lipids on the characteristics, penetration, and stability of resveratrol nanostructured lipid carriers (NLC). Nanostructured lipid carriers (NLC) were made with high shear homogeneous technique. To determine the characterization of NLC, diffraction scanning calorimetry, X-ray diffraction, and Fourier transforms infrared spectrophotometry were used. Examination of the morphological form was carried out with a transmission electron microscope. The particle size and polydispersity index examination were measured by the Delsa Nanoâ„¢ particle size analyzer, while the efficiency of trapping resveratrol in the NLC system was measured by the dialysis membrane method. Furthermore, the penetration depth test on the skin of mice was done by fluorescence microscope method using rhodamine B markers. Physical stability test was performed by examination of particle size and index polydispersity for 30 days. The formula with liquid soy bean oil and oleic acid liquid lipids improved the characteristics including the effectiveness of entrapment and colloidal stability. However, the formula with soy bean oil and oleic acid combination liquid lipids did not provide better penetration into the skin than the use of single liquid lipids. While the formula with soy bean oil and oleic acid liquid lipids proved to improve the physical stability for 30 days.